Peter Robinson. (4th August 2018) - Rossdale, Peter; Hunt, Michael; Peace, Colin; Ricketts, Sidney; Digby, Nicholas Wingfield; Greet, Timothy; Steven, Neil; Pilsworth, Robert; McGladdery, Andrew; Carson, Deidre; Barrelet, Frederic; Shepherd, Michael; et al.
Abstract : A vet with extraordinary compassion – his care about patients' wellbeing, and the consideration he had for concerned farmers or upset pet owners was second to none.